PERI-INTRAVENTRICULAR HEMORRHAGE IN PRETERM INFANTS: THE IMPORTANCE OF SCREENING BY TRANSFONTANELLAR ULTRASOUND - Mirela Elena Ritivoiu; Florin Nicolaie Brezan; Cosmina Cristea; Ioana Codreanu; Diana Goran; Lucica Ghita; Ioana Alina Anca (Amaltea Medical Publishing House, 2013)
Objectives. In preterm babies, peri-intraventricular hemorrahges (PIVH) might cause various degrees of neuropsycho-motor impairment. A 4-year prospective study (2009-2012) performed in the IOMC, was aimed to determine the prevalence of different degrees of PIVH diagnosed by head ultrasound (HUS) among 160 admitted preterm babies, the associated risk factors, along with the neuro-developmental effects on a 12-month follow-up period. Material and methods. In the above-mentioned period all admitted preterms were examined by transfontanelar ultrasound according to a standardized protocol based on Papile's PIVH classifi cation. For those preterms included in the study a 12-month systematic neurologic follow-up was performed. Results. PIVH grade I (45%) and II (37,5%) were the most prevalent types. Grade IV PIVH represented 4,4% from all PIVH cases. The good neurological outcome of grade I and II PIVH, was found to be statistically signifi cant (p < 0.01) for both types. Severe neurological sequelae were associated with grade III and IV and a statistically signifi cant correlation (p<0.01) was found only for grade IV hemorrhages. Conclusion. Systematic HUS screenings for all preterm babies is useful for early diagnosis and PIVH staging, for neurologic outcome prediction, providing the appropriate management strategy and a well-suited parental counseling.